Pengabdian Masyarakat - Pengukuran Indeks Massa Tubuh dan Lingkar Perut dalam Upaya Pemetaaan Obesitas Sentral pada Warga Masyarakat di Desa Dalung, Serang, Banten - Alexander Halim Santoso; Yohanes Firmansyah; Jeffry Luwito; Bruce Edbert; Stanislas Kotska Marvel Mayello Teguh; Alicia Herdiman; Chalishah Shifa Martiana; Tiffany Valeri Alexandra (BADAN PENERBIT STIEPARI PRESS, 2023)
The global prevalence of obesity has increased significantly in the last five decades. Obesity is associated with a higher mortality rate compared to malnutrition. Obesity is a risk factor for non-communicable diseases such as type 2 diabetes mellitus (type 2 DM), cardiovascular disease, metabolic syndrome, chronic kidney disease (CKD), dyslipidemia, hypertension, non-alcoholic fatty liver disease, certain types of cancer, obstructive sleep apnea (OSA), osteoarthritis, and depression. Reports from the World Obesity Federation, estimated one billion people in the world are obese, where 1 in 7 men are obese, and 1 in 5 women are obese. Anthropometry is a method of measurement that is simple, fast, cheap and internationally accepted. Anthropometry is widely used for the initial diagnosis of overall body fat and central obesity. Dalung Village is one of the villages in the Cipocok Jaya District, Serang Regency. This service activity is aimed at getting an overview of obesity in the adult community in the village of Dalung, Serang, Banten so that further prevention efforts can be planned. This activity is designed using the P-D-C-A (Plan-Do-Check-Action) framework. Based on measurements, the prevalence of central obesity in adult males ≥18 years was 44% and in adult females ≥18 years was 60%. The results obtained require follow-up in order to prevent an increase in the prevalence of central obesity and also the incidence of metabolic syndrome.